2018
DOI: 10.1111/adb.12660
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol affects circadian clock core complex and its regulation in microglia cells

Abstract: Cannabis is often used by consumers for sleep disorders. Studies show that circadian rhythm could be affected by a misuse of cannabis. Recent research has connected the role of microglial cells with psychiatric disorders such as substance abuse. The aim was to show the effect of two major components of cannabis on circadian genes regulation in microglial cells. In BV-2 microglial cells, cannabidiol (CBD) induces a deregulation of circadian genes with (P-value = 0.039) or without (P-value = 0.0015) lipopolisacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 57 publications
0
19
1
Order By: Relevance
“…Moreover, preclinical intracerebral perfusion of CBD could prevent sleep rebound after total sleep deprivation (Murillo-Rodriguez et al, 2011) and increase wakefulness in the lights-on period, supporting a clinical alerting effect for this agent in managing somnolence (Babson et al, 2017;Murillo-Rodriguez et al, 2006;Scuderi et al, 2009). On the other hand, CBD-induced sedation has been shown both in animal and human studies, supposedly because of a corticotropin releasing hormone (CRH)-related gene downregulation (Lafaye et al, 2018;Russo et al, 2007). In a study using a PTSD-mice model, CBD microinjected in amygdala both reduced anxiety and reversed REM blockage associated with anxiety (Hsiao et al, 2012).…”
Section: Sleep Disorders Backgroundmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, preclinical intracerebral perfusion of CBD could prevent sleep rebound after total sleep deprivation (Murillo-Rodriguez et al, 2011) and increase wakefulness in the lights-on period, supporting a clinical alerting effect for this agent in managing somnolence (Babson et al, 2017;Murillo-Rodriguez et al, 2006;Scuderi et al, 2009). On the other hand, CBD-induced sedation has been shown both in animal and human studies, supposedly because of a corticotropin releasing hormone (CRH)-related gene downregulation (Lafaye et al, 2018;Russo et al, 2007). In a study using a PTSD-mice model, CBD microinjected in amygdala both reduced anxiety and reversed REM blockage associated with anxiety (Hsiao et al, 2012).…”
Section: Sleep Disorders Backgroundmentioning
confidence: 97%
“…it is associated with decreasing time to sleep onset at low dosages and increasing time at high dosages (Babson et al, 2017;National Academies of Sciences, Engineering, and Medicine, 2017;Zuardi et al, 2008). CBD may possibly act on circadian clock genes and melatonin production (Lafaye et al, 2018). Moreover, preclinical intracerebral perfusion of CBD could prevent sleep rebound after total sleep deprivation (Murillo-Rodriguez et al, 2011) and increase wakefulness in the lights-on period, supporting a clinical alerting effect for this agent in managing somnolence (Babson et al, 2017;Murillo-Rodriguez et al, 2006;Scuderi et al, 2009).…”
Section: Sleep Disorders Backgroundmentioning
confidence: 99%
“…While there is no link between Clock genes and cannabis addiction, the expression of dopaminergic D2 receptor gene (DRD2) is Clock-controlled and may be involved in cannabis addiction by co-expression with the CB1 receptor gene [9]. Interestingly, circadian rhythm genes in microglia were dysregulated by CBD, but not by THC, consistent with its use to treat insomnia [28]. However, high (15 mg) dose of THC acts as a sedative in healthy volunteers while a similar dose of CBD has alerting properties, and counteracts the sedative properties of THC [29].…”
Section: Interactions Between the Ecs And Exogenous Cannabinoidsmentioning
confidence: 99%
“…Chronic cannabis use could implicate an abnormal glia-neuron communication, as observed in a significant dysregulation of circadian genes, with upregulation in Arntl and downregulation of Clock genes. Circadian genes in microglia were dysregulated by CBD regardless of LPS stimulation due to the upregulation of Arntl/Bma1, which maintained microglia in a state of early awakening, whereas negative regulation of Per1 blocks the natural cycle of the cell, maintaining the cell in perpetual morning state [28].…”
Section: Interactions Between the Ecs And Exogenous Cannabinoidsmentioning
confidence: 99%
“…In a recent issue of Addiction Biology, we read, with great interest, the article written by Lafaye et al describing the deregulation of circadian clock genes in BV‐2 microglial cells upon cannabidiol (CBD) treatment. Specifically, the authors have observed, in the presence or absence of lipopolysaccharide stimulation, an upregulation of certain clock genes such as Bmal1 , which is one of the most important elements of the core clock machinery together with increased expression of atf4 , atf5 , and rora as well as downregulation of another key clock gene, clock . CBD derived from Cannabis sativa has anti‐inflammatory and antioxidant activity and shows antiproliferative activity.…”
mentioning
confidence: 99%